1997
DOI: 10.1046/j.1365-2141.1997.2493066.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful second bone marrow transplant for Fanconi's anaemia following escalation of conditioning

Abstract: Summary. Allogeneic bone marrow transplantation represents the treatment of choice for severe bone marrow failure in patients with Fanconi's anaemia (FA). In view of the increased sensitivity to alkylating agents documented in this condition, much attention has focused on reducing the conditioning chemotherapy. We present a 13-year-old girl in whom sibling allogeneic BMT after conditioning with lowdose cyclophosphamide only resulted in graft rejection.However, a second transplant using the same donor proved su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Haematopoietic growth factors (Nemunaitis et al , 1990; Weisdorf et al , 1995), either granulocyte colony‐stimulating factor or granulocyte–macrophage colony stimulating factor, modification of the host immunological status (Ljungman et al , 1996), infusion of autologous frozen stem cells (Mehta et al , 1996; Fouillard et al , 1998) or donor leucocytes (Godder et al , 1998; Remberger et al , 1998), and second allogeneic SCT are the main therapeutic options that can be proposed in case of graft failure. Data on second allogeneic SCTs in this context are scarce (Davies et al , 1994; Miniero et al , 1996; O'Donnell et al , 1997; Grandage et al , 1998), especially in patients with malignant diseases. A recent retrospective study from the Seattle group, including 44 patients with AA who received a second transplant for graft failure between 1970 and 1996, has confirmed that a graft‐versus‐host disease (GVHD) prophylaxis combining cyclosporin A (CsA) and methotrexate was a major predictor of outcome after second transplant (Stucki et al , 1998).…”
mentioning
confidence: 99%
“…Haematopoietic growth factors (Nemunaitis et al , 1990; Weisdorf et al , 1995), either granulocyte colony‐stimulating factor or granulocyte–macrophage colony stimulating factor, modification of the host immunological status (Ljungman et al , 1996), infusion of autologous frozen stem cells (Mehta et al , 1996; Fouillard et al , 1998) or donor leucocytes (Godder et al , 1998; Remberger et al , 1998), and second allogeneic SCT are the main therapeutic options that can be proposed in case of graft failure. Data on second allogeneic SCTs in this context are scarce (Davies et al , 1994; Miniero et al , 1996; O'Donnell et al , 1997; Grandage et al , 1998), especially in patients with malignant diseases. A recent retrospective study from the Seattle group, including 44 patients with AA who received a second transplant for graft failure between 1970 and 1996, has confirmed that a graft‐versus‐host disease (GVHD) prophylaxis combining cyclosporin A (CsA) and methotrexate was a major predictor of outcome after second transplant (Stucki et al , 1998).…”
mentioning
confidence: 99%
“…Sustained engraftment has been observed even in the presence of significant HLA allo-antibodies in two (P1-SIB1 and P3-VUD1) out of the four patients, a well-recognised risk factor for graft failure. 22 Moreover, two prominent features in our patients, extensive malformations and the use of androgens before transplant, have previously been associated with a worse outcome. 15 Furthermore, one of the patients (P3-VUD1) had significant iron overload and abnormalities of liver function at the time of SCT.…”
Section: Discussionmentioning
confidence: 99%
“…5 In this case report, we describe a patient who experienced a second rejection episode after a second allogeneic stem cell transplantation for FA, and who was successfully treated for the second rejection episode by a well-tolerated donor lymphocyte infusion.…”
Section: Discussionmentioning
confidence: 96%